A high protein low glycemic index diet has no adverse effect on blood pressure in pregnant women with overweight or obesity: a secondary data analysis of a randomized clinical trial - Larson, Elisabeth A.; Magkos, Faidon; Zingenberg, Helle; Svare, Jens; Astrup, Arne; Geiker, Nina R. W. (Frontiers in Nutrition, 2023)
Objectives. The objective of this analysis was to evaluate the effect of a diet rich in animal protein and low in glycemic index on blood pressure during pregnancy.Design: This post-hoc, secondary data analysis of a randomized controlled trial, evaluated blood pressure in pregnant participants who were randomized either to an ad-libitum diet with high protein and low glycemic index, rich in dairy and seafood, or an ad-libitum control diet according to national recommendations.The study occurred in pregnant women in Copenhagen, Denmark Sample: 279 pregnant females with overweight or obesity were enrolled.Methods and outcome measure: Blood pressure was measured at 5 timepoints during pregnancy from gestational week 15 through week 36, and blood pressure between groups was compared.Results There were no differences between diet arms in systolic or diastolic blood pressure over time. There were also no differences in most blood-pressure-related pregnancy complications, including the prevalence of premature birth, preeclampsia, or hypertension, but the frequency of total cesarean sections was lower in the active than the control group (16 out of 104 vs. 30 out of 104) (p=0.02).Increased animal protein intake was not associated with changes in blood pressure in pregnant women with overweight or obesity.